Epitaxial Growth of High Quality GaN Films on Lattice Matched Metallic Layers. (13th April 2015) - Dabiran, Amir M; Machuca, Francisco; De, Indranil; Weiss, Robert
Abstract : We discuss the development of high-quality ZrTi metal layers that are epitaxially deposited by sputtering on sapphire and Si, and which are c-axis oriented and lattice matched for growth of low-defect hexagonal GaN films. We also explain and discuss the nucleation and growth of thick GaN layers by molecular beam epitaxy (MBE) and metal organic chemical vapor deposition (MOCVD) on these metal layers. Finally, we present the results of thin-film measurements to demonstrate the high crystal qualities and very smooth surface morphologies of highly specular GaN layers grown on ZrTi buffers in this work.